LusRegTes: A Regression Testing Tool for Lustre Programs - Nguyen Thanh Binh; Trinh Cong Duy; Ioannis Parissis (International Journal of Electrical and Computer Engineering (IJECE), 2017)
Lustre is a synchronous data-flow declarative language widely used for safety-critical applications (avionics, energy, transport...). In such applications, the testing activity for detecting errors of the system plays a crucial role. During the development and maintenance processes, Lustre programs are often evolving, so regression testing should be performed to detect bugs. In this paper, we present a tool for automatic regression testing of Lustre programs. We have defined an approach to generate test cases in regression testing of Lustre programs.  In this approach, a Lustre program is represented by an operator network, then the set of paths is identified and the path activation conditions are symbolically computed for each version. Regression test cases are generated by comparing paths between versions. The approach was implemented in a tool, called LusRegTes, in order to automate the test process for Lustre programs.